Hubungan Antara Bermain Aktif Dengan Perkembangan Sosial Pada Anak Pra-Sekolah Usia 4-6 Tahun Di TK AR Rohmah Bekasi Barat : The Relationship Between Active Play and Social Development in Pre-School Children Aged 4-6 Years at AR Rohmah Kindergarten, West Bekasi - Laikiok, Sinthia; Mariyani (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Prenatal up to 8 years is a golden period because a child's brain development is up to 80%, so it is the best time to develop a positive and potential personality to become an adult. Active play is an activity carried out by a person in order to get pleasure and satisfaction from the activities he does himself.1 Children's social development is the ability possessed by children related to the way children behave in their social life according to community values ​​so that children can become useful individuals in community life.2  Methods: Quantitative with a research design using a cross-sectional approach the sample in this study were all parents of students at AR Rohmah Kindergarten West Bekasi as many as 45 parents the sampling technique was total sampling.  Results: Active play yielded good results for 34 (75,6%) respondents, while 4 (8.9%) respondents were not good. While good social development is 2 (4,4%) respondents, while respondents with poor social development are 5 (11,1%) respondents. Hypothesis testing using Chi-Square obtained a p-value of 0,000 (P < 0,05).  Discussion: There is a significant relationship between active play and social development in preschoolers aged 4-6 years at AR Rohmah Kindergarten West Bekasi in 2022.